2010
DOI: 10.1016/j.exger.2010.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2-dependent IL-23 production in aged murine dendritic cells

Abstract: CD4+ T cells of the Th17 subtype are over-represented in the aged immune system. Dendritic cells (DC) play a critical role in naive CD4+ T cell differentiation. However, expression of cytokines by aged DC that promote differentiation or survival of Th17 cells has not been extensively investigated. Using bone marrow-derived DC from C57BL/6 mice of different ages we compared cytokine production after DC activation by Toll-like receptor agonists for TLR4 and/or TLR7/8. DC-derived TNF-α and IL-12p70 production and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 46 publications
(84 reference statements)
0
9
0
1
Order By: Relevance
“…In our study, lengthening the time-interval between BCG-prime and Apa-boost was associated with induction of balanced proportions of specific IFN-γ and IL-17-producing cells and heightened frequency of IL-2-producing cells. Previously, the propensity of T-cells to induce IL-17 response has been shown to increase with increasing age 47 , and induction of balanced type-1 and type-17 responses has been shown to correlate with superior protective efficacy of rBCG vaccine 48 . Mucosal Apa-boost (10 μg) during the contraction-phase also enhanced the specific IL-4 response in the lung, regardless of the form of Apa-booster used.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, lengthening the time-interval between BCG-prime and Apa-boost was associated with induction of balanced proportions of specific IFN-γ and IL-17-producing cells and heightened frequency of IL-2-producing cells. Previously, the propensity of T-cells to induce IL-17 response has been shown to increase with increasing age 47 , and induction of balanced type-1 and type-17 responses has been shown to correlate with superior protective efficacy of rBCG vaccine 48 . Mucosal Apa-boost (10 μg) during the contraction-phase also enhanced the specific IL-4 response in the lung, regardless of the form of Apa-booster used.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between the studies may be explained by the differences in model of experiment and cell types. In addition, by using bone-marrow-derived DCs from C57BL/6 mice of different ages, Myer et al have demonstrated that addition of PGE2 significantly increased IL-23 production by aged DCs whereas IL-23 expression by young DCs was unaffected [ 19 ], which indicates that age-related changes in DCs should be revalued. Furthermore, even in the same cell type, there are seemingly contradictory reports that PGE2 differentially regulates Mo-DCs cytokine responses depending on receptor usage [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, PGE2 was found to substantially augment IL-23 production by DCs from aged but not young mice 114 . As IL-23 promotes the differentiation of T helper 17 (T H 17) cells, such increases in PGE2 and IL-23 production might underlie the potential increased predisposition to T H 17 cell responses reported in aged individuals 115, 116 .…”
Section: Ageing and Prr Signal Transductionmentioning
confidence: 94%